CHARACTERIZATION OF QUALITY ON PEDADA FRUIT JELLY CANDY (Sonneratia caseolaris) WITH DIFFERENT ADDITION OF CARRAGEENAN - Pujiastuti, Dwi Yuli; Saputra, Eka; Madinah, Cahaya Putri; Nafa’ah, Uszhaqia Adha Rizki; Nirmala, Dwitha (Jurnal Perikanan Unram, 2025)
Jelly candy is a type of confectionery classified as a soft candy. The main ingredients used in making jelly candy include fruit juice, sugar, citric acid, and gelling agents. Carrageenan is one of the substances used in candy production due to its ability to form gels. The addition of carrageenan at the right concentration will result in jelly candy with a firm texture. The aim of this study was to determine the effect of different addition of carrageenan on the quality characteristics of pedada fruit (Sonneratia caseolaris) jelly candy. This research used a Completely Randomized Design (CRD) with 4 treatments and 5 replications. The treatments were P0 (15 grams of gelatin), P1 (10 grams of carrageenan), P2 (15 grams of carrageenan), and P3 (20 grams of carrageenan). The results showed that the addition of carrageenan had an effect on the physical, chemical, microbiological, and organoleptic characteristics of pedada fruit jelly candy. The treatment with 15 gram of carrageenan produced the best jelly candy according to the Indonesian National Standard (SNI), with the value of gumminess 308.08 gf, hardness 773.49 gf, gel strength 220.75 gf/cm², water content 16.07%, ash content 2.61%, reducing sugar 13.68% and total plate count 1.6×10² cfu/gram